Searching for sustainability : interdisciplinary essays in the philosophy of conservation biology - Norton, Bryan G. (Cambridge University Press, 2003)
This book examines from a multidisciplinary viewpoint the question of what we mean - what we should mean - by setting sustainability as a goal for environmental management. The author, trained as a philosopher of science and language, explores ways to break down the disciplinary barriers to communication and deliberation about environment policy, and to integrate science and evaluations into a more comprehensive environmental policy. Choosing sustainability as the keystone concept of environmental policy, the author explores what we can learn about sustainable living from the philosophy of pragmatism, from ecology, from economics, from planning, from conservation biology and from related disciplines. The idea of adaptive, or experimental, management provides the context, while insights from various disciplines are integrated into a comprehensive philosophy of environmental management. The book will appeal to students and professionals in the fields of environmental policy and ethics, conservation biology, and philosophy of science.